Streamer Influencers and Live Shopping: A PRISMA Systematic Review - Meilisa Alvita; Ferryal Abadi; Unggul Kustiawan; Rina Anindita (Dinasti Publisher, 2025)
This study analyzes the role of streamer influencers in the digital marketing ecosystem through a systematic review of 43 journals using the PRISMA approach. The results show that live streaming and shopstreaming increase audience engagement, build authenticity, and drive purchasing decisions through real-time interaction. Influencer authenticity, entertainment value, and brand credibility are key success factors, while the use of artificial intelligence technology in virtual influencers presents both opportunities and ethical challenges. In addition to its benefits, challenges such as streamer burnout and the need for ethical regulations in digital marketing are also identified. These findings provide valuable insights for developing effective digital marketing strategies.